The Impact of Information and Communication Technology and Financial Development on Energy Consumption: A Dynamic Heterogeneous Panel Analysis for MENA Countries - Dabbous, Amal (International Journal of Energy Economics and Policy, 2018)
This study investigates the impact of information and communication technology (ICT) and financial development on energy consumption for a panel of 11 MENA countries, for the period between 1995 and 2014. Unlike previous studies, this study uses principal component analysis to construct an index for ICT. In addition, the dynamic panel data model is estimated using heterogeneous panel estimation technique that accounts for cross-sectional dependence. The results reveal that there is a positive statistical significant relationship between ICT index and energy consumption. However, financial development did not appear to have an impact on energy consumption. We conclude that while ICT use increases energy consumption, financial markets development did not contribute to the increase in energy consumption. Finally, some policy implications relevant to our empirical results are discussed such as the need for policy makers to formulate appropriate and effective energy conservation policies, as well as to encourage the adoption of more energy saving devices that accompany the increase in the use of ICT in the MENA region. Keywords: ICT, Financial Development, Energy Consumption, MENA Countries. JEL Classifications : Q43, O13, O16, O33, C21